2006
DOI: 10.1007/s11064-006-9178-8
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Mediating Manganese-Induced Toxicity in Human Glioblastoma Cells (U87)

Abstract: Although essential, manganese (Mn) intake in excess leads to neurotoxicity. Mn neurotoxicity induces impairment of energy metabolism and ultimately cell death. Nevertheless, the signaling mechanisms underlying Mn toxicity are unknown. Employing human glioblastoma (U87) cells, we investigated several signaling pathways (ones promoting cellular proliferation and invasion) underlying Mn toxicity. Mn-treatment of U87 cells induced a down-regulation of MAPK pathway but the AKT pathway was not markedly affected. Mn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…As a consequence of its alterations in kinetic properties, it is predicted that the G2019S mutant would remain largely active at physiologically elevated Mn 2+ levels and therefore this putative signaling pathway should be compromised. Although it can be difficult to directly demonstrate altered changes in enzyme activity in vivo as a consequence of alterations in specific ion levels, some in vivo studies have shown that elevated Mn 2+ levels can decrease the activity of some kinases (Puli et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of its alterations in kinetic properties, it is predicted that the G2019S mutant would remain largely active at physiologically elevated Mn 2+ levels and therefore this putative signaling pathway should be compromised. Although it can be difficult to directly demonstrate altered changes in enzyme activity in vivo as a consequence of alterations in specific ion levels, some in vivo studies have shown that elevated Mn 2+ levels can decrease the activity of some kinases (Puli et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although it can be difficult to directly demonstrate altered changes in enzyme activity in vivo as a consequence of alterations in specific ion levels, some in vivo studies have shown that elevated Mn 2+ levels can decrease the activity of some kinases (Puli et al 2006). Direct in vivo studies of the proposed model of the effects of Mn 2+ on WT and G2019S LRRK2 kinase activity are complicated by the many conflicting studies of the effects of LRRK2 on signal transduction pathways and the lack of robust specific in vivo markers of LRRK2 activity (Biskup and West 2008;Greggio and Cookson 2009;Webber and West 2009), but in vivo studies of Mn 2+ affects on LRRK2 kinase activity are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other than their effect of depressing the mitochondrial respiratory chain, thereby decreasing oxidative phosphorylation, treatment of U87 cells with silicon dioxide nanoparticles could also lower survival of U87 cells through altering cell signaling pathway(s) that regulate(s) cell survival and proliferation. 20 We therefore investigated this possibility by examining the effect of these nanoparticles on expression of ERK and phosphorylated ERK proteins. We observed that when U87 cells were treated with silicon dioxide nanoparticles 1-50 µg/mL for 48 hours, the protein expression of phosphorylated ERK showed a dose-related decrease, while that of ERK protein remained essentially unchanged ( Figure 6), suggesting that a lowering of this cell survival/proliferation signaling mechanism could, at least in part, account for the dose-related decrease in U87 cell survival induced by these nanoparticles.…”
mentioning
confidence: 99%
“…Consistent with the results of a previous study [54], our results show that Mn 2þ enhanced pFAK expression, suggesting enhanced ECM-integrin interactions. Moreover, to examine the effect of MnAuNPs on the neuronal differentiation pathway, the phosphorylation of extracellular signalregulated kinase 1 or 2 (ERK1/2), which is a critical downstream signaling protein in the p38 mitogen-activated protein kinase (MAPK) pathway and NGF signaling pathway, was examined [55]. The expressions of phophorylated ERK1/2 and cdc42, a protein implicated in neural development [56], in PC12 cells were upregulated in the MnAuNP, free Mn 2þ , and NGF with starvation groups (Fig.…”
Section: Resultsmentioning
confidence: 99%